2021
DOI: 10.1038/s41467-021-21482-z
|View full text |Cite
|
Sign up to set email alerts
|

Water enables mild oxidation of methane to methanol on gold single-atom catalysts

Abstract: As a 100% atom-economy process, direct oxidation of methane into methanol remains as a grand challenge due to the dilemma between activation of methane and over-oxidation of methanol. Here, we report that water enabled mild oxidation of methane into methanol with >99% selectivity over Au single atoms on black phosphorus (Au1/BP) nanosheets under light irradiation. The mass activity of Au1/BP nanosheets reached 113.5 μmol gcatal−1 in water pressured with 33 bar of mixed gas (CH4:O2 = 10:1) at 90 °C under lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 34 publications
5
165
0
1
Order By: Relevance
“…53,54 The mechanism of the photocatalytic conversion of CH 4 to CH 3 OH was explored in the presence of water, and the results showed that water can be used as a catalyst to assist in O 2 activation. 55 Zhou et al 56 introduced 36 water molecules and a constant potential correction to construct a real electrochemical environment, which emphasized the importance of hydrogen bond networks for stabilizing reaction intermediates. Wang et al 57 reported the basic mechanism of the interaction between liquid water as a hydrogen source on a metal-free carbon nitride catalyst and oxygen, as well as the reaction mechanism of H 2 O 2 synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 The mechanism of the photocatalytic conversion of CH 4 to CH 3 OH was explored in the presence of water, and the results showed that water can be used as a catalyst to assist in O 2 activation. 55 Zhou et al 56 introduced 36 water molecules and a constant potential correction to construct a real electrochemical environment, which emphasized the importance of hydrogen bond networks for stabilizing reaction intermediates. Wang et al 57 reported the basic mechanism of the interaction between liquid water as a hydrogen source on a metal-free carbon nitride catalyst and oxygen, as well as the reaction mechanism of H 2 O 2 synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges for the preparation of SMACs is the high tendency to agglomerate into clusters or nanoparticles with the increment of mass loading. In order to solve this issue, the introduction of uniformly distributed coordination sites, such as N, 46,149,[213][214][215][216][217][218][219] O, [220][221][222][223][224][225] S, 47,[226][227][228][229][230] P, 48,231 or their combinations, [232][233][234][235][236] is a widely-recognized strategy to attract and fix metal SAs by intensifying the metalsupport interaction. Differing from defect anchoring, coordination attraction does not necessarily need defects.…”
Section: Coordination Attractionmentioning
confidence: 99%
“…Hence, the single-atom modifications could be applied to regulate the dynamics of photogenerated charge transfer by shortening the charge migration distances and endowing strong interactions between metals and carriers ( Gao et al, 2020 ). For example, the Zeng and Li group designed the single-atom Au-modified black phosphorus (Au 1 /BP) nanosheet catalyst for the selective oxidation process of methane to methanol ( Luo et al, 2021 ). Under light irradiation, 1 O 2 generated by Au 1 /BP could react with water, forming adsorbed P-OH and P-OOH.…”
Section: Single-atom Modificationmentioning
confidence: 99%